Building Responsiveness and Customer Satisfaction: Communication Strategies of the Customer Service Unit of Perumda Tirta Giri Nata in Cirebon City - Prastika, Gilang Widyas; Trisandi, Aditya Yoan; Imawan , Khaerudin (Green Publisher Indonesia, 2025)
This study aims to analyze the application of Grunig and Hunt's Two-Way Symmetrical Model of communication in customer complaint services at Perumda Tirta Giri Nata Kota Cirebon. This communication model emphasizes balanced and mutually beneficial two-way communication between organizations and the public. The study employs a descriptive qualitative approach, with data collected through observation, documentation, and interviews with customers. The results indicate that Perumda has successfully established a responsive complaint communication system through both offline and online channels, such as direct service at the complaint unit, Instagram, WhatsApp, and email. Complaint handling is conducted systematically and followed up by relevant administrative and technical units, using a transparent and participatory approach. In addition, innovative strategies such as complaint priority scales, pipe replacement programs, payment facilitation, and water supply crisis management further reflect the application of symmetrical communication principles. The reciprocal relationship and customer participation in the problem-solving process demonstrate the success of Perumda in fostering ethical, open, and mutually beneficial communication. Therefore, the implementation of the Two-Way Symmetrical Model at Perumda Tirta Giri Nata has made a positive contribution to improving service quality and building customer trust.